2013
DOI: 10.1038/bjc.2013.728
|View full text |Cite
|
Sign up to set email alerts
|

PA28gamma emerges as a novel functional target of tumour suppressor microRNA-7 in non-small-cell lung cancer

Abstract: Background:MicroRNA-7 (miR-7) has been reported to be a tumour suppressor gene. However, whether it has a role in the growth of non-small-cell lung cancer (NSCLC) and what is its target involved in the tumour growth is still under investigation.Methods:NSCLC tissue sample, NSCLC cell lines and tissue microarray were investigated in this study. Total RNA, miRNA and protein were used for RT-PCR and western blot analysis. Immunohistochemistry was performed in tissues microarray. Cell culture and intervention expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 55 publications
3
38
0
Order By: Relevance
“…The relative expression of miR-7 was also assessed by qPCR in 39 lung cancer and 8 normal lung tissue specimens. Consistent with previous findings (14), the relative expression of miR-7 decreased significantly in lung cancer tissues compared with that in normal lung tissues (data not shown). Notably, we found that the expression level of miR-7 in lung cancer tissues with mutation sites was lower compared with that in lung cancer tissues without mutation sites (Fig.…”
Section: Promoter Mutation Is Associated With Repressed Expression Ofsupporting
confidence: 92%
See 2 more Smart Citations
“…The relative expression of miR-7 was also assessed by qPCR in 39 lung cancer and 8 normal lung tissue specimens. Consistent with previous findings (14), the relative expression of miR-7 decreased significantly in lung cancer tissues compared with that in normal lung tissues (data not shown). Notably, we found that the expression level of miR-7 in lung cancer tissues with mutation sites was lower compared with that in lung cancer tissues without mutation sites (Fig.…”
Section: Promoter Mutation Is Associated With Repressed Expression Ofsupporting
confidence: 92%
“…In lung cancer, recent evidence demonstrated that the expression of miR-7 is decreased in cancer tissues (14). Moreover, miR-7 was found to inhibit the growth and metastasis of lung cancer cells and induce their apoptosis (21).…”
Section: Promoter Mutation Is Associated With Repressed Expression Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiong’ et al showed that miR-7 inhibited the growth of human non-small cell lung cancer A549 cells through targeting BCL-2 [14]. The same research group also identified PA28gamma as a novel functional target of tumour suppressor microRNA-7 in non-small-cell lung cancer [45]. Xu and his colleagues reported that miR-7-regulated TLR9 signaling-enhanced growth and metastatic potential of human lung cancer cells by altering the phosphoinositide-3-kinase, regulatory subunit 3/Akt pathway [46].…”
Section: Discussionmentioning
confidence: 99%
“…6D). In fact, REGγ is reported to be regulated by other signals than mutant p53, the most studied is miR-7 [56][57][58], a tumor suppressor in many cancers. Therefore we suppose REGγ could be upregulated by some undetermined molecules in these p53-negative specimens and cells.…”
Section: Discussionmentioning
confidence: 99%